Intimate partner violence and Primary Health Care services: invisibility and medicalization - Machado, Dinair Ferreira [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP] (FapUNIFESP (SciELO), 2025)
The aim of this study was to identify care strategies used by primary health care professionals in situations of violence against women. We conducted a qualitative study using primary data obtained from interviews with 16 women and secondary data from 14 patient medical records in women’s health services. The findings reveal that health professionals reaffirmed intimate partner violence as a domestic phenomenon limited to private settings and/or medicalized the problem with anti-inflammatory drugs and benzodiazepines. Violence against women was therefore either rendered invisible or medicalized, without ever considering a comprehensive approach to the concept of health and disease.
La violencia contra la mujer por parte de un compañero íntimo en los servicios de Atención Primaria: de la invisibilidad a la medicalización
A violência contra a mulher por parceiro íntimo nos serviços de Atenção Primária: da invisibilidade à medicalização
Keywords: Medicalization; Primary health care; Violence against women